Correctional officer mental health training: analysis of 52 U.S. jurisdictions - Kois, Lauren E. (Criminal justice policy review, 2020)
Research indicates correctional officer (CO) mental health training may be effective in facilitating the safety and security of both inmates and COs. We assessed Department of Corrections’ CO preservice (requisite for beginning an official post) mental health training requirements in 50 states, the District of Columbia, and the Federal Bureau of Prisons. We obtained information regarding instruction method, training duration, and courses required. Descriptive statistics showed that all jurisdictions require mental health training, ranging from 1.5 to 80 hr (M = 13.54, SD = 14.58, Mdn = 8). When considering course titles, the most common course topic is crisis intervention (n = 44, 84.62%). The next most frequent course topics are general psychoeducation (n = 24, 46.15%), special populations (n = 12, 23.08%), specific clinical interventions (n = 7, 13.46%), institutional procedure specific to mental health (n = 6, 11.54%), and CO mental health and self-care (n = 4, 7.69%). Future research should examine whether CO mental health training is related to positive mental health outcomes and other important institutional metrics, as well as variations in training and its impact at the national and international levels.